The Synthesis of TiO2 nanoparticles by Milling and Coprecipitation Mixed Method: Maya Puspitasari Izaak, Yohanes Edi Gunanto, Henni Sitompul, Wisnu Ari Adi - Maya Puspitasari Izaak Maya Puspitasari Izaak; Yohanes Edi Gunanto Yohanes Edi Gunanto; Henni Sitompul Henni Sitompul; Wisnu Ari Adi Wisnu Ari Adi (Jurnal Fisika dan Aplikasinya, 2020)
Ilmenite type Fe2O3 waste (which is processed from natural iron sand) was processed into TiO2 nanoparticles powder carried out by leaching with HCl and then using high-energy milling (HEM) for 50 hours. The characteristics of the powder such as particle size, size distribution and phases were analyzed using various techniques such as XRD, SEM, EDS and particle size analyzer. Synthesis and characterization of ilmenite type iron sand have been successfully made into TiO2 by milling and coprecipitation mixed method. The purity level of TiO2 was obtained by 85.01%. Particle size of TiO2 was approximately 500 nm.